Development and Application of an Aerosol Model Under a Severe Nuclear Accident - Yuan, Xianbao; Wei, Jingyu; Zhang, Binhang; Guo, Yuefeng; Shi, Qiang; Guo, Pan; Yang, Senquan; Tan, Chao (Frontiers in Energy Research, 2022)
Radioactive aerosol will transport in the containment and also will leak into the environment under a severe nuclear accident. Thus, it is of great significance for predicting the behavior of aerosol under a severe nuclear accident. In order to analyze the aerosol behavior, an improved multi-component sectional model is developed, which improves section numbers and updates the aerosol particle density at each time step. The model’s dependability is confirmed to use benchmark and experimental values. An excellent agreement can be observed between simulation and benchmark. On this premise, the LBLOCA accident is chosen to explore the behavior of radioactive aerosol in the containment. The finding shows that the aerosol is mostly deposited on the structure’s surface due to gravity in the LBLOCA accident. According to a comparison of the influence of aerosol natural deposition mechanisms on the distribution of diameter particles, Brownian diffusion, thermophoresis, diffusiophoresis, and gravity all have an effect on aerosol in the range of 0.01 μm–0.03 μm particles, and the deposition of 2 μm–20 μm particles is mainly due to gravity. After comparing and evaluating the influence of aerosol density in the containment, it can be inferred that changed aerosol particle density leads aerosol particles coagulate into larger particles.